Ag(i)-Catalyzed oxidative decarboxylation of difluoroacetates with activated alkenes to form difluorooxindoles. Issue 25 (14th June 2017) - Wan, Wen; Li, Jialiang; Ma, Guobin; Chen, Yunrong; Jiang, Haizhen; Deng, Hongmei; Hao, Jian
Abstract : A silver-catalyzed oxidative decarboxylative gem -difluoromethylenation of difluoroacetates with activated alkenes to gem -difluoromethylenated oxindoles. Abstract : A silver-catalyzed oxidative decarboxylative gem -difluoromethylenation of difluoroacetates with activated alkenes under mild reaction conditions has been developed. This radical cascade reaction provides a new method for the construction of a variety of gem -difluoromethylenated oxindoles.